2012
DOI: 10.1016/j.abb.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

NADPH–cytochrome P450 oxidoreductase: Prototypic member of the diflavin reductase family

Abstract: NADPH-cytochrome P450 oxidoreductase (CYPOR) and nitric oxide synthase (NOS), two members of the diflavin oxidoreductase family, are multi-domain enzymes containing distinct FAD and FMN domains connected by a flexible hinge. FAD accepts a hydride ion from NADPH, and reduced FAD donates electrons to FMN, which in turn transfers electrons to the heme center of cytochrome P450 or NOS oxygenase domain. Structural analysis of CYPOR, the prototype of this enzyme family, has revealed the exact nature of the domain ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
122
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 213 publications
(359 reference statements)
0
122
0
Order By: Relevance
“…Our recent HDX-MS studies provided detailed models of the iNOS output state, but, because the FAD/NADPH subdomain was not included in the truncations used in this study, the relative positioning of the entire reductase and oxidase domains could not be determined (7). Based on the crystal structure of the nNOS reductase domain (8), it has been hypothesized that the reductase domains dimerize in the NOS holoenzyme, but this hypothesis remains a point of major uncertainty and contention (6,19,20). Furthermore, despite significant homology, it is unknown whether all three NOS isoforms adopt a similar overall structure.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…Our recent HDX-MS studies provided detailed models of the iNOS output state, but, because the FAD/NADPH subdomain was not included in the truncations used in this study, the relative positioning of the entire reductase and oxidase domains could not be determined (7). Based on the crystal structure of the nNOS reductase domain (8), it has been hypothesized that the reductase domains dimerize in the NOS holoenzyme, but this hypothesis remains a point of major uncertainty and contention (6,19,20). Furthermore, despite significant homology, it is unknown whether all three NOS isoforms adopt a similar overall structure.…”
Section: Significancementioning
confidence: 99%
“…This binding is thought to release the FMN subdomain from the input state (6). Our recent studies investigating iNOS through hydrogendeuterium exchange MS (HDX-MS) suggested an intermediate state as the enzyme transitions from input to output state (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CPR is important in transferring electrons from NADPH through to the CYP allowing the incorporation of one molecule of oxygen, hence a monooxygenase reaction, to various substrates (Guengerich 2007). CPR is a highly conserved diflavin protein composed of two flavin cofactors, flavin mononucleotide (FMN) and flavin adenenine dinucleotide (FAD), that transfer the electrons one at a time to a CYP (Iyanagi et al, 2012;Lian et al, 2011). Due to the nature of CYP research among mammals and insects, the CPR gene has been isolated from an array of species and been characterized in many of these (Chen and Zhang 2014;Liu et al, 2014;Zhu et al, 2012) however, CPR has not been isolated or characterized from a tick species to date, despite the importance of this protein to the functioning of the monoxygenase complex and subsequent detoxification of xenobiotics.…”
Section: Introductionmentioning
confidence: 99%